Fostering Student Agency to Build a Whole Child, Whole School, Whole Community Approach - Holly Henderson Pinter; Lisa Bloom; Amie Broyhill; Kim K Winter (Middle Grades Review, 2019)
In this practitioner perspective, we explore the concept of student agency through the implementation of a student government association in a laboratory middle school. Interviews with a social studies teacher and her students offer perspectives of the impact of student voice and choice for student experiences. We describe three major lessons learned through this implementation process: students learn to have healthy conflict and cooperative skills; students learn the appropriate processes to enact change in a democratic society; and students learn to conduct service for their peers, school, and community.
Keywords: agency; democratic classroom; voice and choice; middle school; young adolescents